Design and Development of a portable Pulse Oximetry system - A. Zaltum, Mohamed; Ahmad, M. Shukri; Joret, Ariffuddin; Abdul Jamil, M. Mahadi (International Journal of Integrated Engineering, 2010)
Heart is the most important part in human body. Thus, it is important to follow-up and monitor its condition. Heart rate (HR) and blood oxygen saturation (SpO2) are important indicators directly related to heart-pulmonary system. Monitoring of HR and SpO2 offers us a good indication of heart functionality. Therefore, it is crucial to design and develop a homemade inexpensive device for measuring HR and SpO2. Pulse Oximeter (PO) is an opto-electronic non-invasive medical instrument capable of measuring and recording the changes of HR and SpO2 at the finger tip. In this paper we will demonstrate the overall process involved in the development of a portable (PO) system which can be used for health condition monitoring or for educational and research purposes.